Le care en éducation et la posture éthique de l'enseignant : une place pour la valeur-actitude altruisme ? - Tommy Terraz
Our purpose through this article in normative ethics is to show how the approach of care in education requires above all the ethical posture of teacher himself as a care provider. The foundations of the care ethics approach has great positive elements but also some deficiencies to overcome. The article consists to consider the linkages between the focused sensitivity to particular, defended by the ethics of care, and abstract universalism of utilitarian and deontological moral reasoning. We reflexively propose a particular model: a measured virtue ethics for teachers built around value-actitude altruism (EIVVAA in french) in order to allow the emergence of the student as a person. Beyond the traditional oppositions between autonomy/dependence, care/justice, minimalist relativism/abusive moralism, this updated approach of virtue ethics tends to be well-balanced. Better still, it would be the condition of possibility that would make ethics of care in education possible, because it is important, for the teacher, to choose with conscience and reason to practice value-actitude altruism in order to be able to genuinely take care for others.